191k views
3 votes
I need help asap pls and thank you ;)

Given: △KMN, ABCD is a square
KN=a,
MP

KN
, MP=h
Find: AB

I need help asap pls and thank you ;) Given: △KMN, ABCD is a square KN=a, MP ⊥ KN-example-1

1 Answer

6 votes

Answer:


\text{Length of AB is }(ah)/(a+h)

Explanation:

Given △KMN, ABCD is a square where KN=a, MP⊥KN, MP=h.

we have to find the length of AB.

Let the side of square i.e AB is x units.

As ADCB is a square ⇒ ∠CDN=90°⇒∠CDP=90°

⇒ CP||MP||AB

In ΔMNP and ΔCND

∠NCD=∠NMP (∵ corresponding angles)

∠NDC=∠NPM (∵ corresponding angles)

By AA similarity rule, ΔMNP~ΔCND

Also, ΔKAP~ΔKPM by similarity rule as above.

Hence, corresponding sides are in proportion


(ND)/(NP)=(CD)/(MP) \thinspace\thinspace and\thinspace\thinspace (KA)/(KP)=(AB)/(PM) \\\\(ND)/(NP)=(x)/(h) \thinspace\thinspace and\thinspace\thinspace (KA)/(KP)=(x)/(h)\\\\(NP)/(ND)=(h)/(x) \thinspace\thinspace and\thinspace\thinspace (KP)/(KA)=(h)/(x)\\\\(PD)/(ND)=(h)/(x)-1 \thinspace\thinspace and\thinspace\thinspace (AP)/(KA)=(h)/(x)-1\\


KA((h)/(x)-1)=AP


ND((h)/(x)-1)=PD

Adding above two, we get


(KA+ND)((h)/(x)-1)=(AP+PD)


(KN-AD)=(x)/(((h)/(x)-1))


a-x=(x)/(((h)/(x)-1))


a-x=(x^2)/(h-x)


x^2=ah-ax-xh+x^2


x(h+a)=ah


x=(ah)/(a+h)

User ClementWalter
by
5.2k points